Contextual factors influencing the implementation of activity based costing in Iraqi banking sector: a research framework - Al-Nuaimi, Safaa Ibrahim Mahmood; Mohamed, Rapiah; Alekam, Jamal Mohammed Esmail (2016)
Activity-Based Costing (ABC) has been widely identified as a sophisticated cost management technique that is used to manage and reduce cost and improve organizational performance.As such, many organizations from different industries, including the banking industry have focused their attentions towards the implementation of ABC due to the ability of ABC to provide accurate costing information and enhance organizational performance.Also, a sizable number of contingency-based studies have examined the impact of certain contingency factors also known as contextual factors on the process and success of ABC implementation. Although, most of these previous studies have focused on the manufacturing industry little studies have paid attention to the effect of contextual factors in the implementation of ABC in the service sectors, such as banking institutions. Meanwhile, ABC is a costing system that is more pertinent to the service sector and particularly the banking industry. To this end, this paper reviews previous studies on the role of contingency factors such as: organizational culture, information technology, organizational structure, and competition on the implementation of ABC. Subsequently, a conceptual framework is proposed and future researchers are recommended to validate the hypotheses proposed in this research empirically.